Incidence, determinants and consequences of delirium in older patients after transcatheter aortic valve implantation. (24th February 2020) - Goudzwaard, Jeannette A; de Ronde-Tillmans, Marjo J A G; de Jager, Tom A J; Lenzen, Mattie J; Nuis, Rutger-Jan; van Mieghem, Nicolas M; Daemen, Joost; de Jaegere, Peter P T; Mattace-Raso, Francesco U S
Abstract: Background: delirium is an event leading to negative health outcomes and increased mortality in patients. The aim of this study is to investigate the incidence, determinants and consequences of post-operative delirium (POD) in older patients undergoing transcatheter aortic valve implantation (TAVI). Methods: The TAVI Care and Cure program is a prospective, observational registry in patients referred for TAVI at Erasmus University Medical Centre. The presence of delirium was evaluated by daily clinical assessment by a geriatrician pre- and up to 3 days post-TAVI. Mortality data were obtained from the Dutch Civil Registry. Results: A total of 543 patients underwent TAVI between January 2014 and December 2017. Overall, the incidence of POD was 14% (75/543 patients) but declined from 18% in 2014 to 7% in 2017 ( P = 0.009). Patients who developed POD were older (81.9 ± 5.8 versus 78.6 ± 8.3 years, P < 0.001), had higher prevalence of renal dysfunction and prior stroke (54% versus 40%, P = 0.02; 31% versus 18%, P = 0.01) and were more often frail (32% versus 25%, P = 0.02). From a procedural perspective, general anesthesia (odds ratios (OR), 2.31; 95% CI, 1.40–3.83; P = 0.001), non-transfemoral access (OR, 2.37; 95% CI, 1.20–4.70; P = 0.01) and longer procedural time (OR, 1.01; 95% CI, 1.01–1.02; P < 0.001) were significantly associated with POD. One-year survival rate was 68% among patients who had suffered a POD and was 85% in patients without a POD (hazard ratio's 1.8 (95% CI 1.01–3.10), P = 0.045). Conclusion: POD frequently occurs after TAVI and is associated with increased mortality. It might be speculated that patient selection and the minimalistic approach of TAVI may reduce the frequency of delirium.